K Kreasi Tenun Ikat Berbasis Pewarna Alami dalam Pelestarian Warisan Budaya - wayan Oktarini (PT. Penerbit Riset Sadwa, 2025)
The community service activity entitled “Ikat Weaving Creations Based on Natural Dyes in Preserving Cultural Heritage” was carried out at SMA Santo Paulus Weliman, Malaka Regency. This activity was motivated by the increasingly modern lifestyle of today, which often causes the younger generation to forget the importance of preserving local culture, including the use of natural dyes in traditional woven fabrics derived from plants. The program aimed to foster students’ love for local culture through the introduction and utilization of natural dyes obtained from plants. The methods applied included mentoring, training, and hands-on practice, enabling students to not only understand the theoretical aspects but also acquire practical skills in applying natural dyeing techniques to weaving threads. The students were able to identify various sources of natural dyes from their surroundings, such as teak leaves that produce a reddish-brown color, butterfly pea flowers that yield a bluish-purple hue, turmeric that produces yellow, and mahogany bark that provides a brown shade. Therefore, this program serves as a concrete effort to revitalize the cultural heritage of ikat weaving while instilling values of cultural preservation among the younger generation from an early age